Schaftoside from Plumula nelumbinis mitigates “Shanghuo” by inhibiting low‐grade inflammation, diminishing oxidative stress, and enhancing energy metabolism - Zhiqiang Li; Weijie Wu; Ruiling Liu; Huizhi Chen; Lishu Wang; Ben Niu; Honglei Mu; Haiyan Gao; Hangjun Chen (Food Frontiers)
Abstract The study was focused on the therapeutic potential of schaftoside (SS), a key bioactive compound found in Plumula nelumbinis, in the context of “Shanghuo,” an excessive internal heat condition induced by the overconsumption of capsaicin. “Shanghuo” in traditional Chinese medicine is characterized by symptoms like skin and mucous membrane redness, swelling, fever, and discomfort. It is commonly used to describe symptoms such as intense thirst, constipation, and a rapid or surging pulse. In modern medicine, it is associated with various factors, including dietary irritants, stress, gut microbiota imbalances, and immunological issues. The concept of Yin–Yang balance is pivotal in the theory of traditional Chinese medicine. Yin embodies elements of stability and inhibition, whereas Yang is indicative of vitality and assertiveness. Excessive capsaicin intake can also trigger “Shanghuo” symptoms by disrupting the body's balance of “Yin and Yang.” In the present study, we isolated SS from P. nelumbinis and performed in vitro antioxidant assays. SS exhibited a concentration‐dependent increase in antioxidant activity, indicating its potential to combat oxidative stress. In animal experiments, rats exposed to a high dose of capsaicin showed elevated levels of inflammatory markers and reduced antioxidant levels. SS effectively mitigated these imbalances, restored antioxidant enzyme activity, and reduced inflammation. Furthermore, capsaicin‐treated rats showed decreased energy metabolism and altered gut microbiota. SS treatment enhanced energy metabolism and increased the abundance of intestinal flora, highlighting its potential to restore metabolic balance. In conclusion, SS from P. nelumbinis shows promise in alleviating “Shanghuo” induced by excessive capsaicin intake.